SMARTPHONE APPLICATION EFFECTS ON USER’S INTERPERSONAL COMMUNICATION SELF ESTEEM - Eric Stenly (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2021)
The use of a smartphone is no doubt increasing, especially in this digitalization era. Younger people mostly use it because they highly rely on online technologies, as a place to get information faster and mobile, by using various kinds of a smartphone application. There are at least six kinds of smartphone applications’ categorization, such as social networking sites (SNS), gaming, business, education, entertainment, and traveling application. These vary is useful for interpersonal communication in order to fulfill their beliefs, preferences, and emotions through self-esteem. This study aim is to examine the relationship between smartphone application use and interpersonal communication self-esteem based on Maslow’s need. This study was quantitative-descriptive research, collected from active smartphone users using a questionnaire and also a literature study of public journals related to the use of smartphone applications. Smartphone application use was equal to self-esteem quantity in the interpersonal communication field. The various smartphone applications contributed to increasing their interpersonal communication self-esteem.